2006
DOI: 10.4049/jimmunol.177.7.4514
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-Hemorrhage Induces Depressed Splenic Dendritic Cell Functions in Mice

Abstract: Although Kupffer cell, splenic, and peritoneal macrophage functions are markedly altered following trauma-hemorrhage (T-H), it remains unclear whether T-H also affects splenic dendritic cell (sDC) functions. We hypothesized that sDC functions will also be compromised following T-H. Male C3H/HeN (6- to 8-wk) mice were randomly assigned to sham operation or T-H. T-H was induced by midline laparotomy and ∼90 min of hemorrhagic shock (blood pressure 35 mmHg), followed by fluid resuscitation (four times the shed bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 46 publications
(62 reference statements)
4
60
0
1
Order By: Relevance
“…Similar to septic patients, apoptosis was found to be the cause for depletion of dendritic cell in septic mice 21;36;87. Consistent with these studies, findings obtained in our laboratory at two hours after trauma-hemorrhage suggest a suppression in splenic dendritic cell antigen presenting ability and other co-stimulatory functions 44. This was accompanied with decreased MHC class II expression.…”
Section: Sex Hormones and Dendritic Cell Functions Following Trauma-hsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar to septic patients, apoptosis was found to be the cause for depletion of dendritic cell in septic mice 21;36;87. Consistent with these studies, findings obtained in our laboratory at two hours after trauma-hemorrhage suggest a suppression in splenic dendritic cell antigen presenting ability and other co-stimulatory functions 44. This was accompanied with decreased MHC class II expression.…”
Section: Sex Hormones and Dendritic Cell Functions Following Trauma-hsupporting
confidence: 84%
“…This was accompanied with decreased MHC class II expression. Moreover, LPSinduced IL-12 production following trauma-hemorrhage was significantly decreased 44. While the precise mechanism of suppressed dendritic cell function following trauma-hemorrhage remains to be determined, it is likely that a decreases in MHC class II expression and IL-12 production following trauma-hemorrhage may contribute to suppressed dendritic cell antigen presentation.…”
Section: Sex Hormones and Dendritic Cell Functions Following Trauma-hmentioning
confidence: 95%
“…although there are numerous methods to induce trauma and hemorrhagic shock in mice, there are still many drawbacks associated with these methods. according to the method of Chaudry et al [12], a 20 mm midline laparotomy was performed and then closed in order to induce soft tissue trauma. This method may not be relevant to the clinical setting if, for example, the patient is injured in a road traffic accident.…”
Section: Discussionmentioning
confidence: 99%
“…They also have the ability to activate both T helper 1 (Th1) and Th2 cell responses. Our previous studies have shown that trauma-hemorrhage causes a decrease in splenic DCs maturation (Kawasaki et al, 2006). Although treatment with 17β-estradiol following trauma-hemorrhage alters the circulating plasma cytokine levels and improves lymphocyte and macrophage immune functions, it remains unknown whether 17β-estradiol also modulates splenic DC function under those conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of purified splenic CD11c-positive cells to present antigen to D10.G4.1 cloned helper T-cells (ATCC, Manassas, VA) was carried out according to the method as previously described (Kawasaki et al, 2006). In brief, the CD11c-positive cells were incubated for 30 min (37°C, 5% CO 2 , in the dark) with 50 μg/ml mitomycin C (Sigma Chemical Co., St. Louis, MO) following which the cells were washed (4 times) in PBS, and a series of dilutions was made.…”
Section: Antigen Presentationmentioning
confidence: 99%